2015
DOI: 10.1097/aln.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of GAL-021 as a Novel Breathing Control Modulator

Abstract: GAL-021 behaved as a breathing control modulator in rodents and nonhuman primates and diminished opioid-induced respiratory depression without compromising opioid analgesia. It acted predominantly at the carotid body, in part by inhibiting KCa1.1 channels. Its preclinical profile qualified the compound to enter clinical trials to assess effects on breathing control disorders such as drug (opioid)-induced respiratory depression and sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…GAL-021 treatment is noted to have a short duration of action after a bolus injection [1,52]. The major effect of GAL-021 on ionic currents (e.g., I K(Ca) or I K(M) ) shown here also had a rapid onset of action.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…GAL-021 treatment is noted to have a short duration of action after a bolus injection [1,52]. The major effect of GAL-021 on ionic currents (e.g., I K(Ca) or I K(M) ) shown here also had a rapid onset of action.…”
Section: Discussionmentioning
confidence: 51%
“…GAL-021 has recently been developed as a novel breathing control modulator thought to preserve respiratory drive and to protect patients from the respiratory impairment resulting from opioids and other modalities; moreover, it notably did not influence analgesia [1][2][3][4][5][6][7]. The studies have also reported that this agent is an experimental drug demonstrated to inhibit Ca 2+ -activated K + channels with big conductance functionally expressed on type 1 cells of the carotid bodies [1,8,9]. However, to what extent this compound perturbs other patterns of voltage-gated ionic currents has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in Figure 7B, in the continued presence of 3 µM PTER, subsequent addition of neither TRAM-39 (3 µM) nor tolbutamide (10 µM) substantially modified PTER-mediated elevation in the channel opening probability, while that of verrculogen (1 µM) or GAL-021 (10 µM) was capable of reversing the PTER-induced raise in channel activity. GAL-021 is recognized as an intravenous inhibitor of BK Ca channels [54]. For example, further application of GAL-021 (10 µM), but still in the presence of PTER (3 µM), attenuated channel activity from 0.084 ± 0.012 to 0.037 ± 0.009 (n = 8, p < 0.05).…”
Section: Comparisons Of the Effects Of Pter Pter Plus Tram-39 Pter mentioning
confidence: 99%